Sex-Dependent Protective Effect of Combined Application of Solubilized Ubiquinol and Selenium on Monocrotaline-Induced Pulmonary Hypertension in Wistar Rats - Tatyana Kuropatkina; Olga Pavlova; Mikhail Gulyaev; Yury Pirogov; Anastasiya Khutorova; Sergey Stvolinsky; Natalia Medvedeva; Oleg Medvedev (MDPI AG, 2022)
Ubiquinol exhibits anti-inflammatory and antioxidant properties. Selenium is a part of a number of antioxidant enzymes. The monocrotaline inducible model of pulmonary hypertension used in this study includes pathological links that may act as an application for the use of ubiquinol with high bioavailability and selenium metabolic products. On day 1, male and female rats were subcutaneously injected with a water-alcohol solution of monocrotaline or only water-alcohol solution. On days 7 and 14, some animals were intravenously injected with either ubiquinol's vehicle or solubilized ubiquinol, or orally with selenium powder daily, starting from day 7, or received both ubiquinol + selenium. Magnetic resonance imaging of the lungs was performed on day 20. Hemodynamic parameters and morphometry were measured on day 22. An increased right ventricle systolic pressure in relation to control was demonstrated in all groups of animals of both sexes, except the group of males receiving the combination of ubiquinol + selenium. The relative mass of the right ventricle did not differ from the control in all groups of males and females receiving either ubiquinol alone or the combination. Magnetic resonance imaging revealed impaired perfusion in almost all animals examined, but pulmonary fibrosis developed in only half of the animals in the ubiquinol group. Intravenous administration of ubiquinol has a protective effect on monocrotaline-induced pulmonary hypertension development resulting in reduced right ventricle hypertrophy, and lung mass. Ubiquinol + selenium administration resulted in a less severe increase in the right ventricle systolic pressure in male rats but not in females 3 weeks after the start of the experiment. This sex-dependent effect was not observed in the influence of ubiquinol alone.